2017
DOI: 10.1186/s13195-017-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

A selenium species in cerebrospinal fluid predicts conversion to Alzheimer’s dementia in persons with mild cognitive impairment

Abstract: BackgroundLittle is known about factors influencing progression from mild cognitive impairment to Alzheimer’s dementia. A potential role of environmental chemicals and specifically of selenium, a trace element of nutritional and toxicological relevance, has been suggested. Epidemiologic studies of selenium are lacking, however, with the exception of a recent randomized trial based on an organic selenium form.MethodsWe determined concentrations of selenium species in cerebrospinal fluid sampled at diagnosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 101 publications
0
49
1
Order By: Relevance
“…We did not assess the bioavailability of trace elements after food ingestion by determining biological indicators of exposure, although previous studies suggested that only a fraction of total element intake is absorbed, especially in the presence of malabsorption disease (Reilly 2002). In addition, we did not carry out any speciation analysis for the selected elements, in spite of the increasing evidence of the importance of speciation analysis in the exposure assessment of trace elements possibly characterized by either toxicological and nutritional properties/features (Michalke et al 2009(Michalke et al , 2018Ruzik 2012;Vinceti et al 2017). Secondly, we did not differentiate between local and imported samples, hampering the ability to assess such a difference due to geographic origin of products.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess the bioavailability of trace elements after food ingestion by determining biological indicators of exposure, although previous studies suggested that only a fraction of total element intake is absorbed, especially in the presence of malabsorption disease (Reilly 2002). In addition, we did not carry out any speciation analysis for the selected elements, in spite of the increasing evidence of the importance of speciation analysis in the exposure assessment of trace elements possibly characterized by either toxicological and nutritional properties/features (Michalke et al 2009(Michalke et al , 2018Ruzik 2012;Vinceti et al 2017). Secondly, we did not differentiate between local and imported samples, hampering the ability to assess such a difference due to geographic origin of products.…”
Section: Discussionmentioning
confidence: 99%
“…This was complemented by our measurement of cadmium in foods commonly consumed by the study population [22]. Our study additionally benefitted from the recruitment of a representative sample of residents from the Modena municipality [8,54]. The characteristics of our study population are similar to those of the overall Italian and regional population [55,56], strengthening the external validity of our results.…”
Section: Discussionmentioning
confidence: 75%
“…A further cohort study including ALS patients with diseaseassociated mutations (C9ORF72, SOD1, FUS, TARDBP, ATXN2, and TUBA4A) has reported elevated levels of inorganic Se (selenite and selenate), GPX and SELENOP in a patient with the tubulin-related TUBA4A mutation, whereas in the remaining ALS individuals, elevated selenomethionine was observed [36]. Finally, in a recently published study, the increased risk (adjusted hazard ratio of 3.1, 95% confidence interval 1.0-9.5) of developing AD later in life was observed in MCI patients with increased concentration of the potentially toxic inorganic selenium species, selenate, Se(VI), in CSF [150]. The study was conducted in 56 MCI patients; the development of AD was monitored after a median follow-up of 42 months.…”
Section: Human Studies Linking Se Exposure or Supplementation To Neurmentioning
confidence: 85%